IMPROVING STUDENTS’ CRITICAL READING SKILLS THROUGH INQUIRY-BASED LEARNING: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Cut Marlini; Zaki Al Fuad; Muhammad Zulhairi Bin Zubairi (SENSEI RESEARCH CENTER, 2026)
Many students can read but they just accept what is written in the text and do not think critically. Inquiry-based learning can be used to make the students ask questions and find the evidence by themselves. This article discusses how inquiry-based learning can improve students' critical reading skills. The method used is literature review from international journals about inquiry learning and critical reading. The result shows that inquiry-based learning can improve critical reading because the students read with a purpose, ask questions, and support their answer with evidence from the text. But the inquiry must be guided by the teacher, because if the students are left alone they will be confused. Therefore the teacher must give scaffolding and also ask higher level questions.